THE GENETIC ANALYSIS OF FRUIT FIRMNESS AND RELATED TRAITS OF TOMATO - S. B. DAGADE; L. K.DHADUK (The Bioscan, 2015)
Eight tomato genotypes were crossed in partial diallel way to get 28 F 1 s. Resulting F 1 s, their 28 F 2 s and 8 parents were evaluated in RBD for fruit yield and firmness related traits. Genetic components of variances viz., D, H 1 , H 2 , h 2 , F and E along with their standard errors and various ratios studied. Significance of D and H 1 as well as H 2 exposed the influence of both additive and dominant genes in the inheritance of fruit weight, fruit polar diameter and fruit equatorial diameter and fruit yield in F 1 generation.Positive h 2 (135.58 in F 1 and 50.61 in F 2 ) indicated that using heavy fruited parent would result in improvement of fruit weight in positive direction. For pericarp thickness dominance component was significant only in F 2 , which indicated importance of non-additive gene action, but KD/KR ratio (1.14 in F 1 and 1.37 in F 2 ) indicated dominance in both generations. One or two dominant gene or gene groups appeared to control fruit yield and firmness related traits in the present study. Estimates of narrow sense heritability were moderate for fruit weight (39.30 in F 1 ), high for equatorial diameter (53.15 in F 2 ) and polar diameter (113.29 in F 1 ) indicating selection of desired plant types.